Abbott & Costello. The complete Universal Pictures collection. [Discs 3-4] [videorecording (DVD)] - Lubin, Arthur, 1901-1995; Abbott, Bud, 1897-1974; Costello, Lou; Raye, Martha; Bruce, Carol, 1919-2007; Foran, Dick, 1910-1979; Fitzgerald, Ella (Universal Studios Home Entertainment, 2008)
Keep 'em flying: Bud and Lou enlist in the Army Air Corps and get caught up in a love triangle. Ride 'em cowboy: Bud and Lou head to a dude ranch with a western novelist to learn how to be real cowboys. Pardon my sarong: Bud and Lou travel to an uncharted tropical island, where Lou is mistaken for a legendary god. Who done it?: Bud and Lou try to solve a murder at a radio network but become suspects themselves.